Pengembangan Panduan Kompetensi Interprofessional Collaboration Practice di Ruang Rawat Inap - Hellen Sindim; Hanny Handiyani; Cori Tri Suryani; Nurdiana Nurdiana (Journal of Telenursing (JOTING), 2022)
This study aims to identify collaborative practices in inpatient rooms and design improvement proposals according to applicable policies and standards. The method used is a pilot project using the Kurt Lewin stage of change approach. Data was collected through secondary data analysis, interviews, observations and surveys using questionnaires. There were 264 survey respondents consisting of primary nurses and associate nurses. Problem analysis was carried out using a fishbone, preparation of a plan of action, implementation, and evaluation of the structure and discussion based on the literature review. The results showed barriers to interprofessional communication in the inpatient room. The most common barriers between doctors and nurses are patient planning, implementation collaboration, and discharge planning. In conclusion, drafting the IPCP competency guidelines for nurses can support nurses in interprofessional collaboration practice in inpatient rooms. Keywords: Interprofessional Collaboration, Interprofessional Communication, Collaboration Practices